The Influence of Work-Life Balance on Service Quality in Government Apparatus with Job Satisfaction as a Mediator Variable - Lubis, Elida Fitri Khairuna; Lubis, Zulkarnain; Lubis, Rahmi (Journal of Educational, Health and Community Psychology, 2024)
In the government sector, public services are part of the duties of the state apparatus to provide services to the community and loyalty to the state. The quality of government public services is a very important factor in public satisfaction. Employees who have a good work-life balance will provide quality services to the community. Work life balance in employees is influenced by job satisfaction including relationships with colleagues and leaders. Dissatisfaction felt by employees will lead to poor service quality. However, it is not yet known how work-life balance affects service quality. This study aims to examine the effect of work-life balance on employee service quality, through the mediation of job satisfaction. This explanatory quantitative research involved 262 employees in Langkat Regency. Data analysis using the Structural Equation Model (SEM) operated through the SmartPLS program. The results show that job satisfaction mediates the effect of work life balance on employee service quality. The results of this study contribute to the problem of low employee service quality which is influenced by work life balance and mediated by job satisfaction.